Measurement of the transverse momentum distribution of Drell–Yan lepton pairs in proton–proton collisions at √s=13 TeV with the ATLAS detector - Aad, G; Abbott, B; Abbott, DC; Abud, AA; Abeling, K; Abhayasinghe, DK; Abidi, SH; AbouZeid, OS; Abraham, NL; Abramowicz, H; Abreu, H; Abulaiti, Y; et al. (European Physical Journal C, 2020)
This paper describes precision measurements of the transverse momentum $p_T^{\ell \ell }$ ($\ell =e,μ $) and of the angular variable $φ ^{*}_{η }$ distributions of Drell-Yan lepton pairs in a mass range of 66-116 GeV. The analysis uses data from 36.1 fb$^{-1}$ of proton-proton collisions at a centre-of-mass energy of $\sqrt{s}=13\,$TeV collected by the ATLAS experiment at the LHC in 2015 and 2016. Measurements in electron-pair and muon-pair final states are performed in the same fiducial volumes, corrected for detector effects, and combined. Compared to previous measurements in proton-proton collisions at $\sqrt{s}=7$ and $8\,$TeV, these new measurements probe perturbative QCD at a higher centre-of-mass energy with a different composition of initial states. They reach a precision of 0.2$%$ for the normalized spectra at low values of $p_T^{\ell \ell }$. The data are compared with different QCD predictions, where it is found that predictions based on resummation approaches can describe the full spectrum within uncertainties.